2013
DOI: 10.1523/jneurosci.1482-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

A Common Optimization Principle for Motor Execution in Healthy Subjects and Parkinsonian Patients

Abstract: Recent research on Parkinson's disease (PD) has emphasized that parkinsonian movement, although bradykinetic, shares many attributes with healthy behavior. This observation led to the suggestion that bradykinesia in PD could be due to a reduction in motor motivation. This hypothesis can be tested in the framework of optimal control theory, which accounts for many characteristics of healthy human movement while providing a link between the motor behavior and a cost/benefit trade-off. This approach offers the op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
60
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 82 publications
12
60
0
Order By: Relevance
“…Our results are also consistent with the results of Baraduc, Thobois, Gan, Broussolle, and Desmurget (2013), who studied one-dimensional reaching movements by PD patients who had stimulating electrodes surgically implanted in the subthalamic nucleus. The latter study showed that a single optimal control model that minimized total neuromuscular cost (motor effort) could predict the speed of reaching movements by both healthy individuals and PD patients.…”
Section: Discussionsupporting
confidence: 91%
“…Our results are also consistent with the results of Baraduc, Thobois, Gan, Broussolle, and Desmurget (2013), who studied one-dimensional reaching movements by PD patients who had stimulating electrodes surgically implanted in the subthalamic nucleus. The latter study showed that a single optimal control model that minimized total neuromuscular cost (motor effort) could predict the speed of reaching movements by both healthy individuals and PD patients.…”
Section: Discussionsupporting
confidence: 91%
“…Although comprising a relatively small fraction of the general population of dopamine neurons, degeneration of the utility-encoding neurons described here (cells who’s encoding of reward was discounted by predicted energetic expenditures) may contribute to such a defective valuation. This inference is in agreement with clinical findings that parkinsonian bradykinesia reflects an exaggerated sensitivity to a movement’s energetic cost (Mazzoni et al, 2007; Baraduc et al, 2013). …”
Section: Discussionsupporting
confidence: 91%
“…These impairments cannot be explained by intrinsic limitations in motor execution, but rather result from a problem in scaling movement vigor due to a defective valuation of actions in terms of their energetic cost-benefit trade-off (Hallett and Khoshbin, 1980; Berardelli et al, 2001; Baraduc et al, 2013). Although comprising a relatively small fraction of the general population of dopamine neurons, degeneration of the utility-encoding neurons described here (cells who’s encoding of reward was discounted by predicted energetic expenditures) may contribute to such a defective valuation.…”
Section: Discussionmentioning
confidence: 99%
“…This revealed that patients are biased toward slow movements, but also demonstrated that patients can move with the same speed and accuracy as control subjects (recently confirmed in a similar design by reference ). A subsequent study by Baraduc and colleagues allowed subjects to move a 1D joystick to a cued eccentric position without a prescribed range of movement speed . In this version of a free choice, variable‐amplitude operant task (hereafter, a VAO task), they found that untreated PD patients moved at systematically slower speeds, yet their movements were described by control laws that were indistinguishable from non‐PD subjects.…”
Section: Activity In Basal Ganglia Circuits Represents Movement Kinemmentioning
confidence: 99%
“…As a result, much interest has been focused on attempting to account for the mechanisms by which dopamine‐depletion produces the profound deficits in voluntary movement typical of parkinsonism . Bradykinesia, the slowing of movement speed, is directly attributed to the loss of dopaminergic innervation and dopamine replacement therapy using l ‐dopa can ameliorate bradykinesia in PD patients (although movement velocity does not fully recover with dopamine replacement therapy or deep brain stimulation). Further, the presence of augmented dopamine levels increased the speed and amplitude of voluntary movements …”
mentioning
confidence: 99%